Knowledge and practice regarding body mechanics among the nurses in a tertiary hospital of Pokhara, Nepal - Parajuli, Roshni; Lamichhane, Sabina (Journal of Chitwan Medical College, 2026)
Introduction: Body mechanics refers to the efficient, coordinated, and safe use of the body parts during physical tasks. Nursing profession experiences a high incidence of musculoskeletal injuries during patient care. Injuries can be prevented through correct body mechanics. This study aimed to assess the knowledge and practices regarding body mechanics among nurses in a tertiary hospital in Pokhara. Method: A descriptive cross-sectional study was conducted at Pokhara Academy of Health Sciences, Nepal, during 26 Apr 2024 to 09 May 2024, among nurses working in outpatient and inpatient. Ethical approval was obtained. Convenience sampling was used. Knowledge and practices of body mechanics was assessed using a pre-tested, structured self-administered questionnaire. The IBM SPSS was used for descriptive and Chi-square analysis, with significance level set at p<0.05. Result: Out of 105, 38(36.2) nurses had good knowledge of body mechanics. Regarding practice, 84(81.0) demonstrated satisfactory adherence to body mechanics techniques. There was statistically significant association of level of knowledge on body mechanics with working hours/week (p=0.027) and educational status (p=0.006). Conclusion: Nurses exhibited an average level of knowledge but satisfactory practice. Further education on body mechanics is essential to enhance their well-being and prevent occupational injuries.